Декоративні особливості північноамериканських видів роду Crataegus L. - Rubis, V.L. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 1999)
Ornamental peculiarities of 10 species of North-American hawthorn from the collection of “Olexandria” dendropark are described. The dynamics of ornamental features of these species during the year have been determined.